Boosting Research for Health in Libya and Developing Countries. Research Incubtors - Aisha Nasef; Adel El Taguri (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
Research is a search for knowledge and an attempt to find out in a systematically and scientific manner to establish facts. It is characterized by clarity, objectivity, precision, validation, verification and generalizability.